2022
DOI: 10.1175/waf-d-21-0041.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving Wind Speed Forecasts at Wind Turbine Locations over Northern China through Assimilating Nacelle Winds with WRFDA

Abstract: To improve the wind speed forecasts at turbine locations and at hub-height, this study develops the WRFDA system to assimilate the wind speed observations measured on the nacelle of turbines (hereafter referred as turbine wind speed observations) with both 3DVAR and 4DVAR algorithms. Results exhibit that the developed data assimilation (DA) system helps in greatly improving the analysis and the forecast of wind turbine speed. Among three experiments with no cycling DA, with 2-h cycling DA, and with 4-h cycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Both variational techniques rely on minimizing the difference between model forecasts and observations by optimizing a cost function. One work that exploits the benefits of variational data assimilation is by Sun et al (2022), in which wind speed forecasts are improved when assimilating observations from the nacelle of turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Both variational techniques rely on minimizing the difference between model forecasts and observations by optimizing a cost function. One work that exploits the benefits of variational data assimilation is by Sun et al (2022), in which wind speed forecasts are improved when assimilating observations from the nacelle of turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2022) and Nielsen‐Gammon et al (2007) have shown that local ABL wind observations have a positive impact on the analysis of mesoscale models. So far, wind measurements from HAB tracks have never been assimilated into NWP models, and a feasibility study is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…The scaling variables change and the turbulence scheme cannot adequately handle the different flow regimes; for instance, too much mixing will not represent sharp gradients of low-level jets (Bosveld et al, 2014). Sun et al (2022) and Nielsen-Gammon et al ( 2007) have shown that local ABL wind observations have a positive impact on the analysis of mesoscale models. So far, wind measurements from HAB tracks have never been assimilated into NWP models, and a feasibility study is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…Third party observations are data collected by other organizations using meteorological sensors. Examples are wind observations from ground based wind turbines (Sun et al, 2022) and data from Air Traffic Control (ATC). A surveillance radar interrogates aircraft and in case of Enhanced Surveillance (EHS) position, identity, airspeed, Mach number are exchanged (De Haan, 2011), in case of Meteorological Routine Airport Report (MRAR) wind speed and temperature are directly transferred (Strajnar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance too much mixing will not represent sharp gradients of low level jets . Sun et al (2022) and Nielsen-Gammon et al (2007) have shown that local ABL wind observations have a positive impact on the analysis of mesoscale models. So far wind measurements from HAB tracks have never been assimilated in NWP models and a feasibility study is recommended.…”
Section: Introductionmentioning
confidence: 99%